Pengaruh Responsible Leadership terhadap Turnover Intention Melalui Ethical Climate dan Work Motivation - Maharani, Devi Agung; Jatmiko (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Turnover intention has become a major problem for companies in Indonesia with an incidence rate of around 10-12% annually, which has an impact on the decline in the number of human resources and the increasing cost of recruiting and training new employees. Generation Z which dominates the current workforce, shows a high turnover rate due to dissatisfaction with salaries, incentives, benefits, career development opportunities, and an unconducive work environment. This study aims to examine the relationship between responsible leadership, ethical climate, work motivation, and turnover intention among generation Z employees, especially those aged 17 years and over. This study uses a quantitative method with data collection through questionnaires distributed to generation Z employees in various companies in Jakarta with a sampling technique using nonprobability sampling. Data analysis was carried out using the Structural Equation Model (SEM) method. The results of the study showed that responsible leadership has a positive relationship with ethical climate and work motivation. Ethical climate has a negative relationship with turnover intention as evidenced by the decrease in the turnover intention rate. Turnover intention has a negative relationship with responsible leadership and work motivation, thereby increasing employee commitment and loyalty to the company. Therefore, with the increase in responsible leadership and the formation of a good ethical climate, it can be an effective strategy to reduce turnover intention among generation Z employees. The purpose of this study is expected to provide an understanding for company management in formulating policies and strategies on responsible leadership and ethical climate to retain generation Z employees so as to increase work motivation and reduce turnover intention which can ultimately achieve human resource stability and better productivity.